Comparing the Validity of Prospective, Retrospective, and Official Onset for Different Offending Categories - Kazemian, Lila (Journal of quantitative criminology, 2005)
Using data from the Cambridge Study in Delinquent Development, a prospective longitudinal study of 411 London males, the main aim of this research is to compare the age of onset of six types of offenses according to different methods of measurement – prospective self-reports, retrospective self-reports, and official records – and also to explore self-reported and official onset sequences. Results showed that ages of onset reported in retrospective accounts generally tended to be higher than those reported prospectively. Agreement rates between prospective and retrospective accounts were lowest for minor forms of offending, and highest for more serious offenses such as theft of vehicles. Males with heavy substance use habits were less likely to report the same age of onset retrospectively compared with prospectively. Denial rates were substantial in all comparisons, particularly for minor forms of offending. Comparisons between self-reported and official measures of onset revealed that there was a greater degree of agreement between the two measures for serious offenses. Whereas self-reported onset sequences suggested that minor crimes were committed before more serious offenses, official onset sequences suggested the reverse. The findings show that retrospective reports are not suitable to address research questions requiring detailed information (i.e., most criminal career parameters: age of onset, frequency, age of termination, etc.), for studying minor forms of offending, and for samples of individuals with serious substance use habits. Furthermore, official measures of offending can also produce misleading results, particularly when studying minor forms of offending.